Complicated malaria and a covert ruptured spleen: a case report - Waweru, Peter (J Surg Case Rep, 2014)
Spontaneous splenic rupture in complicated malaria is an uncommon cause of hemoperitoneum in the tropics. The exact incidence of splenic rupture is unknown, largely due to under-reporting, but has been estimated at ∼2%. Its pathophysiology is linked to the formation of a subcapsular hematoma. Upon rupture, patients present with features of shock and peritonitis and in most cases (95%), computed tomography (CT) scan detects the splenic injury. Patients should be managed conservatively with splenectomy reserved for patients with shock and hemoperitoneum due to risk of post-splenectomy sepsis. We report the case of a 38-year-old man with severe malaria who presented with fever, chills and abdominal pains. A CT scan abdomen failed to reveal splenic parenchymal injury or any splenic extravasation of contrast. Conservative management was unsuccessful. Exploratory laparatomy confirmed the spleen as the site of bleeding necessitating a splenectomy.